A participação do Movimento Passe Livre nos eventos de junho de 2013: uma análise antissistêmica - Rocha, Fernando Lacerda (Universidade do Vale do Rio dos Sinos, 2023)
The June 2013 demonstrations revealed the Brazilian population's dissatisfaction with the country's political and social conduction. Arising from a series of protests around the world, the demonstrations were orchestrated by the MPL (Movimento Passe Livre/Free Fare Movement) and quickly inflamed Brazilian cities. It brought, at first, the problem of public transport to the public agenda and, later, a series of diffuse agendas. Thus, the history of the Free Fare Movement was decisive for the success achieved in the Demonstrations of June 2013, making it necessary to analyze its contributions to Brazilian society in that period and in the post-June 2013 period, guiding the problem of urban mobility and access to cities. For this, an exploratory study with a qualitative approach was carried out, with the application and analysis of an interview instrument. From the analysis of the interviews, through the theory, it can be seen that the work of the Free Fare Movement was essential for the beginning and the projection of the Demonstrations, with the greatest contribution being didactic: transport was erected as a social right, guiding the problem of urban mobility and access to the cities, making the Unified Transport System proposed; several social movements were created with different agendas; there was learning from various social movements on how to carry out social protest.
Keywords: Movimento Passe Livre; Movimentos antissistêmicos; Manifestações de Junho de 2013; Free Fare Movement; Antisystemic movements; June of 2013 demonstrations; ACCNPQ::Ciências Humanas::Sociologia